Head and neck imaging - Anbarasu, Arangasamy; Lane, Jack ([Oxford] : Oxford University Press, 2018)
An essential introduction to the theory and practice of head and neck radiology, as well as a guide to choosing and performing imaging investigations and minimally invasive procedures.
Previously issued in print: 2018.
Includes index.
Specialized.
Description based on online resource; title from home page (viewed on March 1, 2018).
Keywords: Head -- Imaging; Neck -- Imaging